Therapeutic potential of medicinal plants against COVID-19: The role of antiviral medicinal metabolites. (January 2021) - Khan, Tariq; Khan, Mubarak Ali; Mashwani, Zia-ur-Rehman; Ullah, Nazif; Nadhman, Akhtar
Abstract: There are numerous trials underway to find treatment for the COVID-19 through testing vaccines as well as existing drugs. Apart from the many synthetic chemical compounds, plant-based compounds could provide an array of \suitable candidates for testing against the virus. Studies have confirmed the role of many plants against respiratory viruses when employed either as crude extracts or their active ingredients in pure form. The purpose of this review article is to highlight the importance of phytomedicine against COVID-19. The main aim is to review the mechanistic aspects of most important phytochemical compounds that have showed potential against coronaviruses. Glycyrrhizin from the roots of Glycyrrhiza glabra has shown promising potential against the previously epidemic coronavirus, SARS-CoV. Other important plants such as Artemisia annua, Isatis indigotica, Lindera aggregate, Pelargonium sidoides, and Glychirrhiza spp. have been employed against SARS-CoV. Active ingredients (e.g. emodin, reserpine, aescin, myricetin, scutellarin, apigenin, luteolin, and betulonic acid) have shown promising results against the coronaviruses. Phytochemicals have demonstrated activity against the coronaviruses through mechanisms such as viral entry inhibition, inhibition of replication enzymes and virus release blockage. However, compared to synthetic drugs, phytomedicine are mechanistically less understood and should be properly evaluated before application. Nonetheless, phytochemicals reduce the tedious job of drug discovery and provide a less time-consuming alternative for drug testing. Therefore, along with other drugs currently tested against COVID-19, plant-based drugs should be included for speedy development of COVID-19 treatment.